Pajak dan Retribusi Daerah Serta Dampaknya Bagi Publik - Awaliyah Matondang, Khairani; Fransiska Adelia; Br. Sidebang, Tamaria; Olivia Ginting, Renata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Regional taxes and levies are an important source of regional income to finance the implementation of regional government and regional development. This research aims to examine how the collection of taxes and fees affects what are obstacles to financing and raising funds. The approach used in preparing this research uses literature study, where the data obtained comes from media literature and significant reading with journal titles that are relevant to the topic of discussion. In carrying out this research, researchers used a qualitative description method, this method contains non-numerical data (not numbers). The aim of the journal is to use this qualitative description in accordance with the problem which will discuss regional taxes and levies and their impact on the public, so that we can understand the concept of regional taxes and levies.